Patent Country Selection Strategy for Global Automotive OEMs - Thorslund, Anton; Olsson, Ida (My University, 2025)
In knowledge-based economies, patents play a central role in protecting innovation and enabling strategic positioning. In the automotive sector, characterized by complex products, concentrated innovation clusters, and profound technological transformation, deciding where to file patents is a growing strategic challenge. This thesis explores how a global automotive original equipment manufacturer (OEM) can approach patent country selection in a way that supports the firm’s broader intellectual property (IP) strategy and responds to changes in the competitive and technological landscape. Using a qualitative case study method, data was collected through sixteen semi-structured interviews with internal stakeholders and external IP professionals, complemented by professional literature and practitioner insights. The analysis was guided by Somaya’s (2012) framework of generic patent strategies, proprietary, defensive, and leveraging, along with theories on technological change, innovation ecosystems, and patent strategy. The findings show that market relevance and third-party exposure are the most critical factors in country selection, while legal system quality is treated as a baseline requirement. The strategic intent of the patent portfolio significantly shapes which factors are prioritized. For proprietary strategies, filings focus on key markets; defensive strategies target both own and competitors’ key regions; and leveraging strategies emphasize collaborators’ and suppliers’ geographies. The study also highlights the need for OEMs to dynamically assess IP assertion risk, especially as new technologies attract non-traditional actors into the ecosystem. This thesis contributes to the limited academic literature on patent country selection by offering a strategy oriented approach applicable to automotive OEMs. It emphasizes that country selection decisions should be aligned with the strategic role of each patent portfolio, rather than treated as an isolated administrative task.
Keywords: patent strategy; country selection; international patenting; automotive industry; intellectual property